The psychology of later life : a contextual perspective - Diehl, Manfred; Wahl, Hans-Werner, 1954- (American Psychological Association, 2020)
"Renowned experts in adult development and aging, Manfred Diehl and Hans Werner Wahl synthesize decades of psychological research into a comprehensive volume that considers later life in the context of lifespan development, social and physical environmental factors, and historical-cultural influences. In so doing, they review important research on cognitive functioning, behavioral processes, personality and identity development, and overall well being in middle to late adulthood. Diehl and Wahl's three-part framework helps readers better understand that the development process is influenced by multiple factors and can take many different trajectories. Through this contextualized perspective, they examine the influence that previous life experiences, beginning in early childhood, can have on the aging process in older adults. This includes social relations, technological advances, societal perspectives on aging, and education. The authors also examine the challenges and opportunities of aging, using a strength based approach to promote a diverse, nuanced understanding of successful, healthy aging. Chapters also conclude with dialogues from other experts in the field, offering multiple different perspectives on the research"--